Analyzing Disruptive Conduct among Kathmandu Valley Students: Investigating Student Behavior Patterns - Luitel, Peshal (The Saraswati Review, 2014)
This study investigates disruptive behavior among secondary-level students and examines teachers' perceptions of these behaviors. Using a mixed-methods approach with data triangulation, the research gathers data through interviews, teacher questionnaires, classroom observations, and focus group discussions with students. The qualitative data were thematically analyzed, while quantitative data were subjected to descriptive analysis. The findings indicate that disruptive behaviors—such as inattentiveness, talking out of turn, and classroom disturbances—create significant challenges for teachers, hindering their ability to foster a conducive learning environment. Although some disruptions are perceived as unintentional, they are recognized as a major factor contributing to student underachievement. The study highlights that disruptive behavior not only reflects student indiscipline but also negatively impacts academic performance, teacher effectiveness, and overall school operations. The research emphasizes the critical role of headmasters and teacher training in addressing these behaviors, along with the need for strategies that enhance student motivation and engagement to reduce the frequency of classroom disruptions.